Programma: 16 juli: Helmet; 19 juli: George Clinton; 20-21 juli: Los Lobos; 22 juli: Walter Trout (1993)
Programma: 16 juli: Helmet; 19 juli: George Clinton; 20-21 juli: Los Lobos; 22 juli: Walter Trout.